Evaluation of Information Technology Based Online Learning Needs Assessment in Polytechnic in the Era of Covid-19 - Toyipur Toyipur (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
This research is a needs assessment evaluation which aims to determine the effectiveness of the information technology-based learning program, namely online or online learning to emphasize the difference between the desired or should be or expected conditions (what is) or real / real conditions. in the Covid-19 era with truth and validity data, facts, or information. The research was conducted using mixed methods research or a combination of qualitative and quantitative research in one study with evaluation of "needs assessment", data analysis with descriptive statistics. Collecting data using observation instruments, documentation and questionnaires, distributing questionnaires by means of random or random techniques, data processing refers to the Likert scale with the SPSS program computer The research results from the data on the achievement of class based learning process performance and information technology in 2020 15.78%, while from the research results; the highest score was 88, the lowest score was 50, the mean 66.47, the standard deviation was 11,780, the score scale ranges from 50 to 88, meaning that The effectiveness of online informatics technology-based learning methods in the Covid-19 era can be categorized as unsuccessful according to predetermined learning outcomes